A Case Study of Online Learning Tools to Mitigate the Impact of Covid-19 Pandemic on Education System - K. Sethi, Kamal; Bhanodia, Praveen (International Journal of Computer Sciences and Engineering, 2020)
Pandemics are cruel and devastating. No business, area and affair can be left unaffected or least affected. The entire world is shaken by a pandemic caused by new virus covid-19 since December-2019. This paper describes the broad impact of COVID-19 on educational systems and how the entire learning system is perturbed by the preventive steps taken to curb the spread of the pandemic. Moreover, the evolution of online tools as to continue the teaching learning process has also been illustrated. The study involves use of MOOCS, Moodle and online teaching platforms while conducting academic activities in our Institute from March-June 2020.